Infrastructure project management at the Ministry of Public Education of Costa Rica (MEP) - Víquez-Duarte, Maikol; Orozco-Delgado, Víctor (Innovaciones Educativas, 2020)
Through a historical reconstruction with legal considerations inherent to the reality of those responsible for executing the Costa Rican public administration, the aim is to describe in a practical way the reality of the organization of the administrative staff of a public entity, which has one of the largest payrolls at the Central American level and faces the challenge of attending to what seems like endless management: developing educational infrastructure in the country. After the corresponding documentary review and analysis, a clear intention of the MEP to search for different alternatives to deal with the problems related to the construction and maintenance of the work is evident. However, the problem continues, despite the fact that, since 2012, alternative instruments were used for the construction of school buildings, such as the constitution of a trust for the development of educational infrastructure, which is an important ministerial effort. However, as a first experience and being in compliance with its execution period, the results have not yet been as expected, basically due to the deadline for the delivery of works and the increase in costs initially projected.